PENGARUH PENGGUNAAN APLIKASI MARBEL UNTUK MENGEMBANGKAN KEMAMPUAN MEMBACA - Syifa Mardhiah (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This research aims to determine the application of marble in developing early reading skills. This research is a type of quantitative research using an experimental approach used a pre-experimental research design, which used one group pre-test post-test design. The sample in this study were children aged 5-6 years in Kindergarten B class which are 6 girls and 7 boys. From the data analysis technique using the t-test, obtained the results of using the Marbel application to develop early reading skills for children as obtained from tcount > ttable, which is 8.882 > 1.782. The pre-test and post-test obtained scores that were far apart with the results of the pre-test obtaining an average value of x ̅=5.6, the results of the post-test obtaining x ̅=10.1. In this way the rejection of H0 and Ha is accepted, which means that there is a significant difference between the acquisition of pre-test and post-test scores. Therefore, it can be concluded that the marble application can develop early reading skills in Cinta Ananda Kindergarten